Lipid profiles in users of combustible and electronic cigarettes. (October 2021) - Majid, Sana; Keith, Rachel J; Fetterman, Jessica L; Weisbrod, Robert M.; Nystoriak, Jessica; Wilson, Tabitha; Stokes, Andrew C; Blaha, Michael J; Srivastava, Sanjay; Robertson, Rose Marie; Bhatnagar, Aruni; Hamburg, Naomi M
Electronic cigarette use has especially risen among adolescents and young adults. The aim of this study was to investigate fasting blood glucose and lipid profiles in chronic combustible cigarette and electronic cigarette users. We evaluated participants aged 21 to 45 ( n = 525, mean age 31 ± 7 years, 45% women) without established cardiovascular disease or risk factors who were combustible cigarette users ( n = 290), electronic cigarette users ( n = 131; 65 sole users and 66 dual users), or never users ( n = 104). In the first wave of enrollment (2014–2017), electronic cigarette users reported their products as first, second and third generation devices (e-cig users) and were all largely current (i.e., dual) or former (sole) combustible cigarette users, whereas in the second wave of enrollment (2019–2020), electronic cigarette users all reported pod-based device use (pod users) and included more sole users who were never smokers. In multivariable-adjusted analyses comparing to never users, both sole e-cig users and combustible cigarette users had higher glucose and triglycerides and lower high-density lipoprotein (HDL) cholesterol levels. Dual e-cig users showed higher triglycerides and very-low-density lipoprotein cholesterol, and lower HDL cholesterol compared to never users. In contrast, pod users (both sole and dual) had lipid profiles and glucose levels similar to never users. Overall, users of early generation electronic cigarettes display adverse metabolic profiles. In contrast, pod-based electronic cigarette users have similar lipid profiles to never users. Future studies are needed to understand the cumulative effects of electronic cigarette use on cardiometabolic health.